2018
DOI: 10.1155/2018/8218697
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moderate Aerobic Exercise as Determined by Cardiopulmonary Exercise Testing in ALS

Abstract: Introduction The efficacy of cardiopulmonary exercise testing (CPET) to determining exercise intensity has not been established in Amyotrophic Lateral Sclerosis (ALS). We studied this intervention. Methods We included 48 ALS patients randomized in 2 groups: G1 (n = 24), exercise intensity leveled by CPET; G2 (n = 24), standard care limited by fatigue, during 6 months. ALS functional scale (ALSFRS-R) and forced vital capacity (FVC) were performed every 3 months; CPET was done at admission (T1) and 6 months late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
(34 reference statements)
0
42
0
4
Order By: Relevance
“…A barrier for physicians at the time of data collection was lack of evidence of benefit of exercise. In addition to the results of [16], where no statistical benefit was shown, two other recent exercise trials have reported reduced rates of functional decline associated with aerobic or combined aerobic and strengthening exercise [15,39]. Ideally a metaanalysis and update of the Cochrane review [14] will provide clarity on the issue of benefit of exercise for pALS.…”
Section: Discussionmentioning
confidence: 99%
“…A barrier for physicians at the time of data collection was lack of evidence of benefit of exercise. In addition to the results of [16], where no statistical benefit was shown, two other recent exercise trials have reported reduced rates of functional decline associated with aerobic or combined aerobic and strengthening exercise [15,39]. Ideally a metaanalysis and update of the Cochrane review [14] will provide clarity on the issue of benefit of exercise for pALS.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding these different results in the respiratory and limb motor function scores, we can suggest a possible explanation. Most of ALS patients who were included in meta-analysis study were limb-onset ALS (74.3%, 162/218) (20,24,25). For this reason, we think the patients participated in these studies would have weakness mainly in limb muscles, but less in respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…A barrier for physicians at the time of data collection was lack of evidence of benefit of exercise. In addition to the results of [16], where no statistical benefit was shown, two other recent exercise trials have reported reduced rates of functional decline associated with aerobic or combined aerobic and strengthening exercise [15,39]. Ideally a meta-analysis and update of the Cochrane review [14] will provide clarity on the issue of benefit of exercise for pALS.…”
Section: Limitationsmentioning
confidence: 99%